2022
DOI: 10.2166/wst.2022.030
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution, geochemical behaviors and risk assessment of antimony in rivers around the antimony mine of Xikuangshan, Hunan Province, China

Abstract: Pollutants derived from antimony (Sb) mining can easily cause pollution of surrounding water bodies. However, qualitative source analysis of river pollution is mostly conducted, and quantitative source analysis is still lacking. A total of 21 water samples were collected to analyze the pollution status of the heavy metal element Sb, explore the Xikuangshan (XKS) area river heavy metals pollution mechanism, quantitative analysis the sources of pollution, and carry out irrigation water suitability assessment and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The interrelationships among HMs can provide insights into their sources and migration patterns. A significant correlation between two metals implies a similar origin [83]. Figure 5 illustrate the relationships between different element combinations (As, Cd, Pb and Cu) in various media.…”
Section: Correlation Between Different Elements Across Various Mediamentioning
confidence: 94%
“…The interrelationships among HMs can provide insights into their sources and migration patterns. A significant correlation between two metals implies a similar origin [83]. Figure 5 illustrate the relationships between different element combinations (As, Cd, Pb and Cu) in various media.…”
Section: Correlation Between Different Elements Across Various Mediamentioning
confidence: 94%
“…This mine has a far-reaching impact on the heavy metal pollution of the soil around it. Due to the antimony ore in smelting ore after combustion is easy to concentrate in the dust, through the atmospheric dust accumulation in the soil, so the longer the mining time, the greater the impact of heavy metal pollution on the soil around the mining area Liang et al, 2013;Sheng et al, 2022). However, because the ore composition of the Nandan mining area is more complex than that of the Lengshuijiang mining area, Pb and Cu pollution are also present, compared with the similar As, Cd, Sb, and Zn pollution at Lengshuijiang.…”
Section: Heavy Metal Pollution In Three Mining Areasmentioning
confidence: 99%
“…A recent research survey [4] has indicated the global annual consumption of Sb to be 188,000 tons. The release of Sb and its compounds from natural as well as anthropogenic sources into water bodies is a severe problem in many regions of the world [5][6][7][8]. For instance, the elevated Sb concentrations have been observed as 239 µg/L in Alaska watersheds (USA), 6384 µg/L in Hunan Province rivers (China), and 157 µg/L in Sindh Province lakes (Pakistan), respectively [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%